Adverse Mental Health Impact of the COVID-19 Lockdown in Individuals With Tourette Syndrome in Italy: An Online Survey - Conte, Giulia; Baglioni, Valentina; Valente, Francesca; Chiarotti, Flavia; Cardona, Francesco (Frontiers in Psychiatry, 2020)
During the early stages of the COVID-19 pandemic in Italy, an online survey was launched via a local patient advocacy website to investigate mental health issues in children and adolescents with Tourette Syndrome (TS). Respondents were parents, who were asked to report on their child’s general health, tics, comorbidities/problems, pharmacological treatment/psychotherapy, symptom variations and daily routine as well as on their family’s health and work experiences during the pandemic. 238 people participated in the survey, 203 females and 35 males. Our findings indicate that, in the time window of 4 to 6 weeks after the beginning of the COVID-19-related lockdown, 67% of individuals with TS developed a relevant worsening of the overall clinical condition as rated by their parents. An improvement or no variation of the clinical picture was reported in 20.5% and 6.7% of cases, respectively. Most worsened symptoms included tics, hyperactivity, rage attacks, obsessions/compulsions and anxiety. Of the subjects experiencing a clinical worsening, the majority (51.76%) showed variations across 2-5 symptom domains. No association was found between symptom variation and family demographics or health and economic issues specifically related to the lockdown. The current COVID-19 pandemic is exerting a considerable impact on the mental health of young individuals with TS by worsening both tics and emotional and behavioural symptoms.